Archives of psychiatry research an international journal of psychiatry and related sciences (Zagreb : Department of Psychiatry, University Hospital Center Sestre milosrdnice, 2019)
Časopis o psihijatrijskim istraživanjima i ovisnostima.
Pristup: World Wide Web
Stv. nasl. s nasl. zaslona
Opis prema vol.55,no.1(2019)
Keywords: Psihijatrija -- Istraživanje -- Serijske publikacije